Awareness of the development site of Aedes aegypti larvae - Lubabul Aniq; Suharyo Suharyo; Sukandarno Adi (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Background: dengue fever Dengue (DENGUE HEMORRHAGIC FEVER (DHF) )is a communicable disease that often give rise to Extraordinary Events (of theOutbreak) and a cause of death. The disease is caused by dengue virus carriedby Aedes aegypti mosquitoes as vectors. However, not to know thecharacteristics of the container with the presence of Aedes aegypti larva. Thisresearch would like to compare if there was any relationship between thecharacteristics of the container with the presence of Aedes aegypti larva.Methods: this research is a type of observational analytic study with pieces oflatitude. The population in this research is the whole House which is located inthe city of Semarang. Cluster sampling techniques are used to choose the Housethat there is a case of Dengue Hemorrhagic Fever(DHF), One home index focuscase Dengue Hemorrhagic Fever(DHF) and five houses that are located nearby.The variables examined include the types of containers, container base material,the basic condition of the containers, color containers, container and cover theexistence of the existence of Aedes aegypti larva. Statistical analysis using SPSS16 with the chi square test.Result: there is a relationship between the type of container (p = 0.001<0,05),material container (p=0,001<0,05), basic condition of container (p=0,001<0,05),the color of the container (p=0,004<0,05) with the existence of larva. There is norelationship between the presence of a cover with the existence of larva(p=0,083>0.05).Conclusions: this type of container the most positive Aedes aegypti larva is abath for that community is advised to use this type of container the water onceused up, such as buckets, tubs. If you want to hold the water should be to put asealed water tandon. The selection of base material container should choosebasic materials that are easy to clean. The basic condition for the container mustalways be clean. For the color of the container should select a color other thanblack or dark. In addition it is hoped the community always close the container.Keywords: types, materials, Basic Conditions, Color And Cover Container.